2011
DOI: 10.3390/polym3041575
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Co-Monomer Content on the Swelling/Shrinking and Mechanical Behaviour of Individually Adsorbed PNIPAM Microgel Particles

Abstract: Abstract:The swelling/deswelling behaviour of microgel particles in the bulk and at the surface was studied and correlated to their mechanical properties. We focused on two kinds of particles: pure PNIPAM and PNIPAM-co-AAc particles. It was shown that the two step volume phase transition found for PNIPAM-co-AAc particles in the bulk disappears after the adsorption at the surface and only a one step transition was identified. The transition temperature increased strongly with increasing the co-monomer content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 30 publications
12
111
2
Order By: Relevance
“…Previous studies have shown that the addition of hydrophilic co-monomers to poly(NIPAm) results in decreased temperature sensitivity of the resulting nanoparticles as the charged groups serve to increase overall solubility and resist the temperature-induced hydrophobic collapse (39,52,53). The addition of multiple hydrophilic groups to the backbone of our particles presents a possibility that their temperature sensitivity could be reduced to the extent that they are no longer a viable mechanism of controlled drug loading and release.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that the addition of hydrophilic co-monomers to poly(NIPAm) results in decreased temperature sensitivity of the resulting nanoparticles as the charged groups serve to increase overall solubility and resist the temperature-induced hydrophobic collapse (39,52,53). The addition of multiple hydrophilic groups to the backbone of our particles presents a possibility that their temperature sensitivity could be reduced to the extent that they are no longer a viable mechanism of controlled drug loading and release.…”
Section: Discussionmentioning
confidence: 97%
“…This is explained by microphase separation into pure PNIPAM domains and PNIPAM-co-AAc domains, which exhibit different VPTT. At the surface, such domains interfere with each other due to compression leading to an averaged VPTT [26]. The question arises, whether a geometrical confinement, like a planar surface, might affect the cononsolvency behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the soft nature of the HA/PLL films, the microgels might be spontaneously immersed into the film. The increase in detected width above VPTT might be due to an increase in the elastic modulus of the microgel from about 100 kPa to about 800 kPa, 46,69 which makes the detection of microgels easier by using the AFM. The value of Young's modulus of the surrounding HA/PLL film is in the range of tens of kPa.…”
Section: Molecular Transport Through Mg-coated Ha/pll Filmsmentioning
confidence: 99%
“…44,45 Poly(N-isopropylacrylamide) (PNIPAM) is one of the most well-known temperature sensitive polymers applied for the synthesis of macrogels and microgels (MG). [46][47][48][49] At the volume phase transition temperature (VPTT at 32-34 1C) PNIPAM chains undergo a reversible volume phase transition (VPT) mainly due to intramolecular hydrophobic interactions resulting in the release of bound water molecules and a pronounced volume reduction. [50][51][52][53][54] The advantage of microgels vs. macrogels is that microgels react much faster to external stimuli (here: changes in temperature) than macrogels and they can be easily processed for film formation compared to macrogels.…”
Section: Introductionmentioning
confidence: 99%